Prenatal ultrasonographic diagnosis of fetal scrotal inguinal hernia: a case report and literature review - Angel Yordanov; Krasimira Zhelyaskova (Clinical and Experimental Obstetrics & Gynecology)
Background: Prenatal inguinoscrotal hernia is a rare condition and currently there are only several reports in the literature. Materials: We present a case of inguinoscrotal hernia in a 37-weeks’ gestation fetus, diagnosed at routine prenatal ultrasound. Surgical anomaly correction was done two months after Cesarian section in 39 weeks’ gestation. Results: We discussed the differential diagnosis of scrotal tumor formations that may occur prenatally. We performed a systematic literature review to provide useful information for the diagnosis and the management of this rare prenatal pathology. Discussion: Inguinoscrotal hernia occurs in both single or multifetal pregnancies with no side predilection; it does not mandate a change in the mode or time of delivery with recommendations for correction shortly after birth. Currently, there are no long-term follow-up data about fertility issues in fetuses with inguinoscrotal hernia in their adolescence.